Valuing people to create value an innovative approach to leveraging motivation at work - Mathe, Herve. (World Scientific Pub. Co., 2012)
Motivation, that is positively weaved into the organizational culture, plays an instrumental role in the success of a company as well as in talent retention. This book aims to provide readers with a comprehensive and practical understanding of motivation by exploring the theories of motivation. It also focuses on innovative practices of leading organizations that are known for positive management relations with their employees. It also presents Motivation Spectrum - a dynamic tool, designed by the authors, that can be leveraged by organizations and managers to motivate people positively and to foster a relationship of value among employees and employers.